URGENSI METODE WAFA DALAM PEBAIKAN TAJWID AL-QUR’AN - Ainil Maqsuri (IQRO: Journal of Islamic Education, 2018)
This research discusses how the Urgency of the Wafa Method in improving the Qur'anic Tajweed at the Integrated Islamic Elementary School (SDIT) of Madani Palopo Kec. Wara Selatan. This type of research is descriptive qualitative, using normative, pedagogical, psychological, and sociological approaches. Data consisting of primary and secondary data, which data can get through observation, interviews and documentation. Then, it was analyzed by deductive, inductive and comparative techniques. The results of the study concluded that: 1) The ability to read the Koran by using tajweed in students was not satisfactory. The students still not understanding which is characterized by how to invite and read the Koran based on the rules of recitation. Based on the results, most of the students still lack understanding of how to read the Qur'an based on the rules of recitation.2) The urgency of the Wafa method in improving reading the Qur'an using tajweed is very influencing the reading and intonation of the Koran. Therefore, the wafa method is very relevant to the process of improving reading the Qur'an. 3) Obstacles of the implementation of learning recitation are the various types of wafa, there are those who have been able to read the Koran and also those who do not understand the Koran itself, while most who have been able to read the Koran are still lack of knowledge about its tajweed. The solution for these problems, the students must be discipline in using the wafa Method, the way the teacher conveys the Qur'an properly and correctly using the wafa method.